The Global Trachoma Mapping Project: Methodology of a 34-Country Population-Based Study. (June 2015) - Solomon, Anthony W.; Pavluck, Alexandre L.; Courtright, Paul; Aboe, Agatha; Adamu, Liknaw; Alemayehu, Wondu; Alemu, Menbere; Alexander, Neal D. E.; Kello, Amir Bedri; Bero, Berhanu; Brooker, Simon J.; Chu, Brian K.; et al.
ABSTRACT Purpose: To complete the baseline trachoma map worldwide by conducting population-based surveys in an estimated 1238 suspected endemic districts of 34 countries. Methods: A series of national and sub-national projects owned, managed and staffed by ministries of health, conduct house-to-house cluster random sample surveys in evaluation units, which generally correspond to "health district" size: populations of 100, 000–250, 000 people. In each evaluation unit, we invite all residents aged 1 year and older from h households in each of c clusters to be examined for clinical signs of trachoma, where h is the number of households that can be seen by 1 team in 1 day, and the product h × c is calculated to facilitate recruitment of 1019 children aged 1–9 years. In addition to individual-level demographic and clinical data, household-level water, sanitation and hygiene data are entered into the purpose-built LINKS application on Android smartphones, transmitted to the Cloud, and cleaned, analyzed and ministry-of-health-approved via a secure web-based portal. The main outcome measures are the evaluation unit-level prevalence of follicular trachoma in children aged 1–9 years, prevalence of trachomatous trichiasis in adults aged 15 + years, percentage of households using safe methods for disposal of human feces, and percentage of households with proximate access to water for personal hygiene purposes. Results: In the first year of fieldwork, 347 field teams commenced work in 21 projects in 7 countries. Conclusion: With an approach that is innovative in design and scale, we aim to complete baseline mapping of trachoma throughout the world in 2015.